Teori dan Aplikasi Suhbah dalam Membangun Adab Perspektif Tarekat Tijaniyah - Muhammad Thoriqul Islam (Program Pascasarjana UNU Surakarta, 2023)
The covid-19 pandemic has influenched the educational processes, such as the change from ofline learning to online learning. These situations impact student’s etique because they still need role models in thinking, speaking, and acting. One of the alternative solutions is suhbah. According to Tijaniyah Tariqa, suhbah is a teacher-student approach that characterized by the spiritual initiation use of khirqah as the birth identity of a suluk expert. This research aims to describe the theory and the application of suhbah from the perspective of Tijaniyah Tariqa. The type of this research was library research from several works of Tijaniyah Tariqa and from other related documents. The results of the research are: (1) Theory of suhbah from Tijaniyah Tariqa's perspective is a teacher-student approach by purifying students through wirid lazimah, wirid wazifah, and wirid hailalah, which is characterized by spiritual initiation and use of khirqah to achieve ma'rifatullah, (2) Application of suhbah from Tijaniyah Tariqa perspective could be done through two approaches, namely vertical approach and horizontal approach, (3) The theory and application of suhbah in building the adab from Tijaniyah Tariqa perspective are to transform the student's bad morals into good moral character and reach the level of ma'rifah by practicing wirid lazimah, wirid wazifah, and wirid hailalah.